P146 Undertaking an integrated nurse led review (INCLUDE) for patients with inflammatory conditions: does it change management of morbidities?. (20th April 2020) - Hider, Samantha; Machin, Annabelle; Bucknall, Milica; Cooke, Kendra; Jinks, Clare; Healey, Emma; Finney, Andrew; Cooke, Kelly; Wathall, Simon; Mallen, Christian; Chew-Graham, Carolyn
Abstract: Background: People with inflammatory rheumatological conditions (IRCs), including rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), polymyalgia rheumatica (PMR) and giant cell arteritis (GCA), are at an increased risk of common comorbidities, such as cardiovascular disease (CVD), osteoporosis and mood problems, which result in poorer patient outcomes. The INCLUDE study assessed the feasibility of conducting a randomised controlled trial (RCT) of a nurse-led, holistic, integrated review in primary care. Methods: A pilot cluster RCT was delivered across four general practices. Patients with a Read code for an IRC were recruited by postal invitation. In intervention practices (n = 2), eligible patients were invited to attend a nurse-delivered INCLUDE review - an integrated consultation assessing CVD risk (QRisk2), bone health (FRAX) and mood (PHQ2 and GAD2), using a study-specific computerised template. Patients received an individualized patient management plan, including signposting to additional services as appropriate. Medical record review was undertaken (in consenting participants) at 12 months. We compared primary care contacts (which include consultations, letters and test results) and prescribing rates (of antihypertensives, lipid-lowering, osteoporosis and antidepressant/anxiety medication) at baseline and 12 months. Results: 333 patients participated in the study. The mean (SD) age was 68.2 (13.4) years and 200 (60%) were female. Of these 172 (52%) had RA and 88 (26%) had PMR. 154 (46%) reported high blood pressure, 70 (21%) existing anxiety/depression and 37 (11%) osteoporosis. Medical record data was available for 299/333 participants. Participants in intervention practices had more primary care contacts (mean 29 vs 22). Over the 12-month follow-up, there was higher prescribing of all medication classes in participants in intervention practices (see Table), particularly so for osteoporosis medication (baseline 29% vs 12 month 46%). Conclusion: Nurse-delivered integrated reviews for patients with IRCs identified a significant comorbidity burden. Practices undertaking these reviews had higher prescribing rates at 12 months following treatment of previously un-identified conditions, suggesting that patients with IRCs would benefit from an integrated care review to identify and manage common morbidities. Disclosures: S. Hider None. A. Machin None. M. Bucknall None. K. Cooke None. C. Jinks None. E. Healey None. A. Finney None. K. Cooke None. S. Wathall None. C. Mallen None. C. Chew-Graham None.